Synthesis, Antibacterial Activity And Cytotoxicity Of New Fused Pyrazolo[1,5-a]pyrimidine And Pyrazolo[5,1-c][1,2,4]triazine Derivatives From New 5-aminopyrazoles - Siti Noor Adnalizawati Adnan; Wedad M. Al-Adiwish; M.I.M. Tahir; Siti Farah Hashim; Nazlina Ibrahim; W.A. Yaacob (Elsevier, 2024)
Indexed by Scopus